The Affecting Factors to Grade of Breast Cancer in Dr. Soetomo Hospital of Surabaya - Ulfa Aulia; Arief Wibowo; Hari Basuki Notobroto (Health Notions, 2018)
Prognosis of cancer depends on variables, other factors, the stage of cancer, the biological warfare and general conditions when the cancer is diagnosed. Social status, economic status, and demographic issues choose in determining the stage of cancer when the patient first comes to the hospital. The purpose of this study to examine the role, nutritional status, and family history with breast cancer patients in Dr. Soetomo hospital. The study conducted in this study was a non-reactive or non-intrusive method. The sample in the analysis using simple random sampling with sample size of 95 patients. Does not contain the effect of variables associated with grade of breast cancer with p-value 0.795. While for variable of nutritional status and family history with cancer to breast cancer level with p-value 0.033 and 0.005. The p-value in the fitting information table was 0.003 model which contains not only the intercept that was not displayed. The value of Nagelkerke 0.157 or 15.7% means that variable cost, nutritional status and family history with cancer can be used only by 15.7%. From the existing variables was 2 significant variables, namely nutritional status with p-value 0.033 and family history with cancer with p-value 0.005. While time did not significantly influence breast cancer rate with p-value 0.795. Keywords: Grade of breast cancer, Age, Nutritional status, Family history